Peningkatan Kapasitas UMKM Melalui Sosialisasi Digital Marketing dan Optimalisasi Media Bisnis di Desa Pasirnangka - Rizqi Nur Rachmawati; Ibrahim Tri Nugroho; Siti Nurlita; Alvin Anggarda Putra; Muhamad Indra Sholahudin (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The limited digital literacy and low online visibility of micro, small, and medium enterprises (UMKM) in Desa Pasirnangka have hindered their ability to compete in an increasingly digital marketplace. This community service program was designed to address these challenges by strengthening the digital marketing capacity of local business owners. The main objective of the initiative was to introduce practical digital promotion strategies and improve the use of online business tools that can enhance customer reach. The program was implemented through a series of socialization sessions, structured training, and hands-on practice, which included creating Google Maps business points, setting up WhatsApp Business profiles, and designing promotional banners. The results show a significant increase in participants’ understanding of digital marketing concepts, alongside their ability to independently create digital business assets. These improvements contributed to better online discoverability and increased confidence among UMKM in utilizing digital platforms for business development. The program demonstrates that targeted digital literacy interventions can generate meaningful and sustainable impacts on local economic empowerment.